Transformasi Fungsi Dan Kedudukan Kejaksaan Agung Dalam Menghadapi Tantangan Reformasi Hukum Di Indonesia - Wijayanto, Fajar; Holijah, Holijah (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2025)
ABSTRACT; This study discusses the transformation of the role and position of the Attorney General in facing the challenges of legal reform in Indonesia. Since the 1998 reform, Indonesia has undergone significant changes in its legal system, and the Attorney General, as one of the main law enforcement agencies, has been confronted with major challenges in adapting to these dynamics. With a broader mandate post-reform, the Attorney General not only functions as the public prosecutor but also as a supervisor of government policies and state administration. This research adopts a normative approach to examine relevant regulations and evaluate the role of the Attorney General in the Indonesian judicial system. The findings indicate that, despite the transformation, there are still significant challenges such as unclear roles, transparency issues, and political influence affecting the Attorney General’s duties. Therefore, the Attorney General needs to strengthen human resource capacity, maintain independence, and optimize technology to enhance the effectiveness of law enforcement in Indonesia.